Payment issues in Malaysia industrialised building system (IBS): Literature visit - Mohd Nawi, Mohd Nasrun; Mydin, Md Azree Othuman; Nursal, Ahmad Taufik; Abdul Nifa, Faizatul Akmar (AENSI Publisher, 2015)
The development of Industrialized Building System (IBS) project involves close relationship between various players such as clients, contractors and manufactures. A good payment mechanism will lead an effective integration and collaboration among player automatically will efficiently achieve the project goal.Although efforts has been undertaken to enhance the IBS practice in Malaysia, the adoption of IBS is still not achieve the government target.This is due to some issues regarding of current payment mechanism. Unlike the conventional approach, the adoption of IBS required a strong cash flow among the project stakeholders especially the contractors in order to ensure project on progress.Current practice, unfortunately, some of the IBS projects are still use the traditional payment method (which is based on in-situ progress claim).This practice is one of the main barriers that affect to the IBS implementation in Malaysia.Therefore, the purpose of this paper through literature review is to explore the issue of payment mechanism in order to enhance the adoption of Malaysian IBS projects in future.